Pengaruh Sikap terhadap Implementasi Green Accounting pada Perusahaan Sektor Pariwisata - Christina Verawati Situmorang; Arthur Simanjuntak (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The transition to Green Accounting is considered a major driver of sustainable economic development. Growing awareness of environmental costs and integration into corporate performance reporting has led to the development of a new environmental dimension of accounting. Although it is a modern concept, its transition into the tourism sector is important, especially since the tourism sector is recognized as energy and emissions intensive. Because environmental preservation can create an optimal framework in the function of sustainable tourism development in Indonesia. This research addresses and analyzes the level of knowledge of the tourism sector about the application of environmental concepts, especially through social and business responsibilities. Research is carried out by applying model classification to data obtained by surveying employees and owners of tourism sector companies in North Sumatra. This method has shown that socio-demographic factors have a significant impact in understanding the importance of green accounting in the tourism sector in Indonesia especially in North Sumatra and that most companies engaged in the tourism sector include corporate social responsibility in their business strategies and policies. The fact that similar or similar research on this topic has not been conducted in developing countries, suggests an important contribution this paper may have to the scientific and professional community, especially in the form of incentives to create and publish reports on environmental preservation.